Unitary Error Bases: Constructions, Equivalence, and Applications - Klappenecker, Andreas; Roetteler, Martin (Proceedings Applied Algebra, Algebraic Algorithms and Error-Correcting Codes (AAECC-15), of Lecture Notes in Computer Science, 2003)
Unitary error bases are fundamental primitives in quantum computing, which are instrumental for quantum error-correcting codes and the design of teleportation and super-dense coding schemes. There are two prominent constructions of such bases: an algebraic construction using projective representations of finite groups and a combinatorial construction using Latin squares and Hadamard matrices. An open problem posed by Schlingemann and Werner relates these two constructions, and asks whether each algebraic construction is equivalent to a combinatorial construction. We answer this question by giving an explicit counterexample in dimension 165 which has been constructed with the help of a computer algebra system.